COMPARISON OF ACID NUMBERS IN BULK AND PACKAGED COOKING OIL SAMPLES - Liany Carolina Rambu Lika; Sahda Sabilah Luhtansa; Septiana Berbara Blaon; Riong Seulina Panjaitan (Department of Pharmacy, Muhammmadiyah University of Sumatera Barat, 2022)
Palm cooking oil is a food ingredient with a main composition of triglycerides, with or without chemical changes. The amount of free fatty acids determines the quality of cooking oil, which can have bad effects on humans. This study aims to determine the quality of oil in packaged cooking oil and bulk cooking oil with treatments based on acid number, acid content, and degree of acidity. Commercial and bulk packaged cooking oils were used in this study. This research method uses acid-base titration with phenolphthalein (PP) as an indicator. The results of this study indicate that the ingredients of bulk cooking oil and packaged cooking oil, when determining the acid number and free fatty acid content, meet the quality standards of SNI 01-3741-2013, namely each acid number 0.6 mg KOH/g and acid content 0.3%.